PENELITIAN TINGKAT KEPUASAN PELANGGAN SEBAGAI PREDIKTOR TERHADAP TINGKAT KESETIAAN PELANGGAN PROVIDER HANDPHONE - Muhammad Nur Nasution (Universitas Trisakti, 2002)
Customer satisfaction has been an integral partof mission and goal ofimost organizations in order to be able to face tough competition. The customer feels satisfied if the product is much better than his expectation. Based on the data taken from